Efficacy of Bio-rational insecticides against Perilla leaf moth on sweet basil (Ocimum basilicum) - KUMAR, ASHOK; SWAMINATHAN, R; MAHLA, M K; AHIR, K C; CHOUDHARY, R S; KACHHAWA, D; KUMAWAT, KAVITA (The Indian Journal of Agricultural Sciences, 2022)
The present study was carried out during kharif 2016–18 at Agronomy Farm, Rajasthan College of Agriculture, MPUAT, Udaipur. The Perilla leaf moth, Pyrausta panopealis Walker (Lepidoptera: Pyralidae) is an important and major insect pest of sweet basil, therefore, ecofriendly bio-rational insecticides were evaluated against perilla leaf moth in the present experiment. The experiment was laid out in uniformly sized plots measuring 12 m2 (4 m × 3 m) in Randomized Block Design containing six treatments and four replications. The treatment schedule comprised two sprayings, the first 15 days after transplanting and the second 45 days after transplanting. The different treatments, viz. Azadirachta indica oil (3%) followed by Bacillus thuringiensis (1.5 kg/ha); NSKE (5%) followed by Spinosad 45SC (150 ml/ha); Azadirachtin 1500 ppm (1%) followed by Lambda Cyhalothrin 4.9 CS (1 L/ha); Pongamia pinnata oil (3%) followed by Cypermethrin 10 EC (0.005%); Nicotine Sulfate 40 S (0.02%) followed by Deltamethrin 2.8 EC (0.015%) and Untreated control. Among the treatments, the Azadirachtin 1500 ppm (1%) was most effective against perilla leaf moth at 3, 5 and 7 days after first spray. After second spray the Spinosad 45 SC (150 ml/ha) was superior treatment against perilla leaf moth at 3, 5 and 7 days; whereas, the Azadirachta indica oil (3%) followed by Bacillus thuringiensis (1.5 kg/ha) was least effective against perilla leaf moth at 3, 5 and 7 days after second spray during both the subsequent years.